Agile Governance in Resource-Limited Settings: Challenges of Bureaucratic Simplification in South-Central Timor - Andayana, Made Ngurah Demi; Pradana, I Putu Yoga Bumi; Toda, Hendrik; Wijayanti, Nadia Sasmita; Rijoly, Jacobus Cliff Diky (Journal Public Policy, 2025)
This study investigates the failure of bureaucratic simplification policy in South-Central Timor Regency, Indonesia, particularly the mandated transition of echelon IV structural roles into functional positions under Permenpan RB No. 17 of 2021. Using a qualitative case study approach, the research collected data through in-depth interviews, participatory observations, and document analysis involving affected civil servants, structural officials, and governance experts. Four interrelated barriers were identified: exclusion of civil servants from decision-making processes, demotivation due to unclear career paths and insufficient financial incentives, stagnant leadership at the echelon II level, and inadequate systemic support, including training and infrastructure. These challenges reflect the interplay of socio-political dynamics and regional resource constraints, which complicate the application of agile governance principles in peripheral regions. The study’s novelty lies in its localized perspective, which reveals governance and administrative complexities often overlooked in mainstream reform narratives. It emphasizes the critical role of leadership behavior, employee involvement, and institutional readiness in sustaining reform, offering practical insights for policy improvement in resource-limited contexts.